ประสิทธิภาพของไมโครแคปซูลน้ำมันตะไคร้เสริมในอาหารต่อสมรรถภาพการเจริญเติบโตและองค์ประกอบซากของไก่เนื้อ - แก้วสันเทียะ, ชโลธร; ศรีธเรศ, นิภารัตน์; เพชรเย็น, ชิราวุฒิ (Thai Journal of Science and Technology, 2020)
The objective of this study was to determine the efficacy of dietary microencapsulated lemongrass oil supplementation on growth performance and carcass composition of broilers. Preparation of lemongrass oil in the form of microcapsules at the ratio of 1 : 1, 2 : 1 and 1 : 2, by using soy protein extract as a wrapper and microencapsulated lemongrass oil using encapsulation technique, followed by drying with a freeze-dried machine, was performed. A total of 96 broiler chickens was raised for 5 weeks, and divided into 4 groups with 4 replications of 6 broilers. Group 1 was a control without lemongrass oil supplementation, and group 2-4 were supplemented with lemongrass oil at a dosage of 200 mg/kg, in the form of microcapsules at the ratios of 1 : 1, 2 : 1 and 1 : 2, respectively. All groups were fed with the same food. The results showed that supplementing with lemongrass oil in the form of microcapsules at the ratios of 1 : 1 and 1 : 2 resulted in lower feed intake and body weight gain, but better feed conversion ratio compared to those of other groups throughout the experiment with a statistical significance (p < 0.01). In addition, the lemongrass oil in the form of microcapsules did not significantly affect the carcass composition of broilers (p > 0.05) at the end of the experiment. The results of the experiment concluded that the supplementation of dietary with lemongrass oil in the form of microcapsules at the ratios of 1 : 1 and 1 : 2 has better feed conversion ratio.